Social Distancing and Quality of Life Among Candidates for the Sports Science Degree During the Covid-19 Pandemic - Burhan Parsak; Leyla Saraç (Pamukkale University, 2022)
This study aimed to examine the relationship between the level of compliance with COVID-19 social distancing measures and the COVID-19 impact on the quality of life of the candidate students in the Faculty of Sports Sciences, based on their gender, whether they are athletes or non-athletes, and whether they are individual athletes or team athletes. The study included 1083 candidate students, including 364 females and 719 males. The Social Distancing Scale and the COVID-19 Impact on Quality of Life Scale were used to collect data. The results showed that the degree of compliance with COVID-19 social distancing measures between athletes and non-athletes was also discovered to differ in favor of non-athletes; and the COVID-19 impact on the quality of life of athletes and non-athletes was similar, being below the average. The level of compliance with COVID-19 social distancing measures in individual or team athletes was higher, and the negative impact of COVID-19 on the quality of life of both groups was below the average. There was no relationship between the level of compliance with COVID-19 social distancing measures and the COVID-19 impact on the quality of life of athletes, and there was a weak negative relationship between the level of compliance with COVID-19 social distancing measures and the quality of life of non-athletes. Because these findings show that people who engage in movement and sports are less affected by COVID-19-related negatives, it is essential not to restrict people's movement and sports activities while taking precautions for COVID-19 and similar emergencies.